Synthesis and Spectroscopic Study for Pt (IV) Complexes with 4-Aminoantipyrine and Sodium Pyrophosphate - Majeed, Sattar R. Majeed; Lateef, Sajid M.; Mohammed, Hanaa A. (Iraqi Journal of Science, 2021)
Pt (IV) complexes were synthesized from 4-Aminoantipyrine (4-AAP) as a primary ligand, and sodium pyrophosphate as a secondary ligand using metal: ligand in (1:1) mole ratio with molecular formula [Pt (4-AAP)Cl4],[Pt (4-AAP)(Pyph)Cl2]. These complexes were characterized by elemental microanalysis (C.H.N), (A.A), [I.R, (U.V–Vis), mass spectroscopy], along with molar conductivity, chloride contents and melting point measurements. The ligands (4-AAP) and (Pyph) gave octahedral geometry with Pt (IV) rapid, simple, sensitive and validated spectrophotometric method has been described for the determination of platinum (IV) using 4-aminoantipyrine. The complex product was quantitatively measured at 385nm and the reaction conditions were studied and optimized.